CHARACTER IDENTIFICATION, GAME’S SATISFACTION, VISUAL AUTHORITY VALUE, MONETARY VALUE, and PURCHASE INTENTION of OVERWATCH GAME ITEM - Tan Alvin Kornelius Tanjaya; Lina Salim (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The game industry is one sector that is developing in this millennial era, this is supported by the high number of players and the high number of esport competitions that have been supported by the Indonesian government. Competition in the gaming industry has also increased and there has been intense competition. One factor that can keep players interested in playing is to add game item features. The purpose of this study is to determine the effect of character identification, game's satisfaction, visual authority value, and monetary value on the purchase intention of Overwatch game items. The data used in this study are primary data obtained through distributing questionnaires to some communities of the Overwatch game. The sample criteria in this study are the millennial generation or those over aged 15 years who are believed to be mature enough, have played the Overwatch game, and have never bought game items. The sampling method used is non-probability sampling (purposive). Four hypotheses are proposed, and all hypotheses are accepted. The character identification, game satisfaction, visual authority value, and monetary value have an influence on the purchase intention of Overwatch game items.